Rewiring the Metabolic Network to Increase Docosahexaenoic Acid Productivity in Crypthecodinium cohnii by Fermentation Supernatant-Based Adaptive Laboratory Evolution - Liu, Liangsen; Diao, Jinjin; Bi, Yali; Zeng, Lei; Wang, Fangzhong; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2022)
To overcome the inhibition caused by the fermentation supernatant in the late fermentation stage of docosahexaenoic acid (DHA)-producing Crypthecodinium cohnii, fermentation supernatant-based adaptive laboratory evolution (FS-ALE) was conducted. The cell growth and DHA productivity of the evolved strain (FS280) obtained after 280 adaptive cycles corresponding to 840 days of evolution were increased by 161.87% and 311.23%, respectively, at 72 h under stress conditions and increased by 19.87% and 51.79% without any stress compared with the starting strain, demonstrating the effectiveness of FS-ALE. In addition, a comparative proteomic analysis identified 11,106 proteins and 910 differentially expressed proteins, including six stress-responsive proteins, as well as the up- and downregulated pathways in FS280 that might contribute to its improved cell growth and DHA accumulation. Our study demonstrated that FS-ALE could be a valuable solution to relieve the inhibition of the fermentation supernatant at the late stage of normal fermentation of heterotrophic microalgae.